(untitled) (Research, Society and Development, 2020)
The objective of the work was obtaining and physical and chemical characterization of the flour product originated from agro-industrial residues, elaborated from drying in an oven and microwave oven (MWO). The acquisition of waste was carried out directly with a concentrated juice manufacturing company, located in the city of Nova Floresta, Paraíba. Thus, several experiments were carried out. The preparation of the flour product in an oven took place at a temperature of 60 ° C for 8 h and presented 8.82% of Water Content (WC), aw 0.53, pH of 4.13, Total Soluble Solids (TSS) of 12 ° Brix, Fixed Mineral Residue (FMR) of 4.51% and Crude Protein (CP) of 6.0%. The heating ramp used to obtain the flour in FMO consisted of 3 cycles of 6 min, totaling 18 min of drying, using 50% of oven power and 50 g of sample. At the end of this process, the product showed 14.01% WC, aw 0.53, pH 4.12, TSS of 11 ° Brix, FMR of 3.31% and CP of 5.24%. The products showed physical and chemical characteristics within the established standards, demonstrating to be a product that can later be used in the formulation of new food products.